Accuracy of a Single, Heparin-Calibrated Anti-Xa Assay for the Measurement of Rivaroxaban, Apixaban, and Edoxaban Drug Concentrations: A Prospective Cross-Sectional Study - Meihandoest, Tamana; Studt, Jan-Dirk; Mendez, Adriana; Alberio, Lorenzo; Fontana, Pierre; Wuillemin, Walter A.; Schmidt, Adrian; Graf, Lukas; Gerber, Bernhard; Amstutz, Ursula; Bovet, Cedric; Sauter, Thomas C.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Applying a single anti-Xa assay, calibrated to unfractionated heparin to measure rivaroxaban, apixaban, and edoxaban would simplify laboratory procedures and save healthcare costs. Aim We hypothesized that a heparin-calibrated anti-Xa assay would accurately measure rivaroxaban, apixaban, and edoxaban drug concentrations and correctly predict clinically relevant drug levels. Methods This analysis is part of the Simple-Xa study, a prospective multicenter cross-sectional study conducted in clinical practice. Patients treated with rivaroxaban, apixaban, or edoxaban were included. Anti-Xa activity was measured using the Siemens INNOVANCE® Heparin assay. Drug concentrations were determined using ultra-high performance liquid chromatography-tandem mass spectrometry (LC-MS/MS). Cut-off levels were determined in a derivation dataset (50% of patients) and sensitivities and specificities were calculated in a verification dataset (50% of patients). Results Overall, 845 patients were available for the present analysis. Correlation coefficients (rs) between the heparin-calibrated anti-Xa assay and drug concentrations were 0.97 (95% CI 0.97, 0.98) for rivaroxaban, 0.96 (0.96, 0.97) for apixaban, and 0.96 (0.94, 0.99) for edoxaban. The area under the receiver operating characteristics curve (ROC) was 0.99 for all clinically relevant drug concentrations. In the verification dataset, the sensitivity was 94.2% (95% CI 90.8-96.6) for 30 µg L-1, 95.8% (92.4-98.0) for 50 µg L-1, and 98.7% (95.5-99.9) for 100 µg L-1. Specificities were 86.3% (79.2-91.7), 89.8% (84.5-93.7), and 88.7% (84.2-92.2) respectively. Conclusions In a large prospective study in clinical practice, a strong correlation of heparin-calibrated anti-Xa measurements with LC-MS/MS results was observed and clinically relevant drug concentrations were predicted correctly.